Reexamination of the identity and status of the termite taxa described by Czerwinski (1901) from southern Brazil (Isoptera: Termitidae) - Constantino, Reginaldo (Zootaxa, 2018)
Czerwinski (1901) (sometimes spelled Tscherwinsky) described four new termite taxa in a publication about the termite collection of the former Zoological Cabinet of the Imperial Warsaw University (currently Museum and Institute of Zoology of the Polish Academy of Sciences, MZPW): Eutermes burmeisteri and Eutermes rippertii iheringi from southern Brazil, Eutermes canariensis from the Canary Islands, and Eutermes nasonovi from Madagascar.